Denture Stomatitis: A Literature Review - Seema Pattanaik; BVJ Vikas; Bikash Pattanaik; Shailendra Sahu; Savita Lodam (Wolters Kluwer Medknow Publications, 2010)
Denture stomatitis is a prevalent and longstanding problem in complete denture wearers. Post denture placement produces significant changes in the oral environment that may have an adverse effect on the integrity of the oral tissues. Mucosal changes could result from a mechanical irritation by the dentures, traumatic occlusion an accumulation of microbial plaque, fungal infection or, a toxic or allergic reaction to components of the denture material. In the present article, various etiological factors contributing to the denture stomatitis and its treatment are reviewed.